Responsiveness and Acceptability for Human Papilloma Virus (HPV) Vaccine Among Parents of Adolescent Girls in Port Harcourt City, Rivers State - Ugochi N, Bright-Okere; Kenneth, Imarenezor Edobor Peter (Darul Yasin Al Sys, 2025)
Human Papilloma Virus (HPV) infections and cervical cancer in Nigeria is of high prevalence. Despite this, the acceptance and utilization of the HPV vaccine which has a high effective preventive measure remain low. The aim of the study was to examine the responsiveness and acceptability of the human papilloma virus (HPV) vaccine among parents of adolescent girls in Rivers State, particularly Port Harcourt City. A descriptive cross-sectional study was adopted for this study. A multi-stage sampling method was used for recruiting a total of three hundred and fifty-seven (357) parents with one hundred and eighty (180) males and one hundred and seventy-seven (177) females used in the study across different age groups (21–60) years for the investigation. The results data obtained using an interviewer based semi-structured questionnaire and the Statistical Package for the Social Sciences (SPSS) version 29 was used in the data analysis. The findings disclosed varying degrees of awareness and understanding of HPV, cervical cancer, and the HPV vaccine, with healthcare providers being the primary source of information 120 (33.6%). Cultural beliefs and religious factors significantly affect vaccine acceptance by 180 (50.4%) and 120 (36.4%) respectively. In terms of Responses on attitude and perceptions regarding safety and efficacy of HPV vaccine, 210 (58.8%) are aware and ready to accept the vaccine, 70 (19.6%) are not ready to take the vaccine while 77 (21.6%) are not sure if they are ready to accept the vaccine. Barriers like cost and accessibility also influence willingness to vaccinate, as findings showed majority of the participants feel the high cost, location and availability of the vaccines is an issue. Statistically, a positive and statistically significant correlation (r = 0.230, p < 0.01) was found between cultural beliefs in the community and the likelihood of vaccinating daughters if religious leaders encourage it. On the other hand, the correlation between cultural beliefs and perceived affordability of the HPV vaccine were negative (r = -0.115, p < 0.05), indicating that parents who consider cultural beliefs in their decision-making may also perceive the vaccine as less affordable, potentially limiting access for financially constrained families. Similarly, there is a positive correlation between the likelihood of vaccinating if religious leaders encourage it and the perceived affordability of the vaccine (r = 0.187, p < 0.01). This suggests that religious influence may reduce the perceived financial barrier, perhaps by increasing the perceived importance of vaccination among parents. Interestingly, the perceived affordability of the vaccine is also negatively correlated with refraining from healthcare services This study in all, revealed important influences between socio-cultural, economic, and service delivery elements in shaping vaccine uptake and emphasizes the need for enhanced education, reduced logistical obstacles, and a focus on addressing cultural concerns to improve both acceptability and accessibility of the HPV vaccine in the study area. Also, the result provides essential baseline data on HPV prevalence among individuals in Port Harcourt City, highlighting the need for continued surveillance and targeted interventions in this area to reduce the risk of HPV transmission.